Gut Microbiota: Potential Therapeutic Target for Sickle Cell Disease Pain and Complications - Tarimoboere Agbalalah; Doofan Bur; Ezinne JaneFrances Nwonu; Adekunle Babajide Rowaiye (Anemia)
Aim. Sickle cell disease has witnessed a 41.4% surge from 2000 to 2021, significantly affecting morbidity and mortality rates, particularly in children from regions with elevated under-5 mortality rates. Gut microbiota dysbiosis is increasingly recognised in SCD, exacerbating complications, particularly chronic pain, marked by significant alterations of proinflammatory bacteria abundance. This review explores the therapeutic potential of Akkermansia muciniphila and Roseburia spp. in alleviating SCD-related complications, emphasising their roles in maintaining gut barrier integrity, reducing inflammation, and modulating immune responses. Method. A literature search up to November 2023 using PubMed, MEDLINE, and Google Scholar databases explored SCD pathophysiology, gut microbiota composition, Akkermansia muciniphila and Roseburia spp. abundance, pain and gut dysbiosis in SCD, and butyrate therapy. Result. A. muciniphila and Roseburia spp. supplementation shows promise in alleviating chronic pain by addressing gut dysbiosis, offering new avenues for sustainable SCD management. This approach holds the potential for reducing reliance on reactive treatments and improving overall quality of life. This research underscores the pivotal role of the gut microbiome in SCD, advocating for personalised treatment approaches. Conclusion. Further exploration and clinical trials are needed to harness the full potential of these gut bacteria for individuals affected by this challenging condition.